Bioremediation of Heavily Contaminated Sandstone from Bida Basin: A pre-emptive model for hydrocarbon exploration in the basin using Bacillus Sustilis and Cereus spp (International Journal of Scientific Research in Science and Technology, 2024)
Petroleum, often known as crude oil, is a complex organic mixture that naturally exists beneath the surface. There is often extreme pollution and other dangerous conditions associated with its exploration, production, refining, storage, and distribution activities. Thus, it is vital to carefully consider the best options after hydrocarbons are found in the Bida Basin, especially in regards to oil spills. In order to prevent this, this study created a preventive model by contaminating samples of sandstone from the Doko Member of the Bida Basin with spent engine oil, which is known to contain a higher percentage of nitrogen and sulfur compounds, aromatic and aliphatic hydrocarbons, and metals like manganese, calcium, zinc, and lead than fresh oils. Two (2) bacterial isolates with a high potential for engine oil biodegradability—Bacillus Subtilis and Cereus—were utilized to assess the effectiveness of total petroleum hydrocarbon (TPH) removal, which is a crucial aspect of crude oil detection. A weekly monitoring program was used to track various physicochemical characteristics of the wasted engine oil, including pH, bacterial biodegradation rate, total petroleum hydrocarbon, nitrate, phosphate, and total organic carbon content. After fourteen and twenty-eight days of contamination, respectively, the test results showed ~50% to
Keywords: Biodegradation Rate; Bida Basin; Bacillus Cereus; Substilis; TPH; Spent Oil